Evaluasi komprehensif program sertifikasi kompetensi instalasi listrik menggunakan model CIPP - Dharmayanthi, I Gusti Made; Rihendra Dantes, Kadek; Luh Gede Erni Sulindawati, Ni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Competency certification programs in vocational education play a strategic role in ensuring graduates’ workforce readiness. However, their effectiveness is rarely examined through a comprehensive evaluation framework. This study aims to evaluate the effectiveness of an electrical installation competency certification program using the Context, Input, Process, and Product (CIPP) model. A program evaluation design with a descriptive quantitative approach was employed, involving 46 graduates of an electrical installation program in 2025. Data were collected through a Likert-scale questionnaire and analyzed using descriptive quantitative statistical methods. The findings indicate that the program was rated effective across all four CIPP dimensions context, input, process, and product with the overall evaluation categorized as highly effective. These results suggest that, structurally and procedurally, the certification program has been implemented in alignment with established evaluation criteria. Nevertheless, several strategic challenges were identified, including limited alignment with current technological developments, low graduate absorption in industry, resource constraints, and limited external recognition of the certification outcomes. Although the program demonstrates strong internal effectiveness, strengthening industry alignment and enhancing the external credibility of certification are essential to ensure meaningful contributions to graduate employability. This study contributes to the discourse on vocational competency assessment by highlighting the importance of integrating internal program quality with external labor market relevance.